Potential Country-level Health and Cost Impacts of Legalizing Domestic Sale of Vaporized Nicotine Products. Issue 3 (May 2019) - Petrović-van der Deen, Frederieke S.; Wilson, Nick; Crothers, Anna; Cleghorn, Christine L.; Gartner, Coral; Blakely, Tony
Abstract : Background: The net impact on population health and health system costs of vaporized nicotine products is uncertain. We modeled, with uncertainty, the health and cost impacts of liberalizing the vaporized nicotine market for a high-income country, New Zealand (NZ). Methods: We used a multistate life-table model of 16 tobacco-related diseases to simulate lifetime quality-adjusted life-years (QALYs) and health system costs at a 0% discount rate. We incorporated transitions from never, former, and current smoker states to, and from, regularly using vaporized nicotine and literature estimates for relative risk of disease incidence for vaping compared with smoking. Results: Compared with continuation of baseline trends in smoking uptake and cessation rates and negligible vaporized nicotine use, we projected liberalizing the market for these products to gain 236, 000 QALYs (95% uncertainty interval [UI] = 27, 000 to 457, 000) and save NZ$3.4 billion (2011 NZ$) (95% UI = NZ$370 million to NZ$7.1 billion) or US$2.5 billion (2017 NZ$). However, estimates of net health gains for 0- to 14-year olds and 65+ year olds had 95% UIs including the null. Uncertainty around QALYs gained was mainly driven by uncertainty around the impact of vaporized nicotine products on population-wide cessation rates and the relative health risk of vaping compared with smoking. Conclusions: This modeling suggested that a fairly permissive regulatory environment around vaporized nicotine products achieves net health gain and cost savings, albeit with wide uncertainty. Our results suggest that optimal strategies will also be influenced by targeted smoking cessation advice, regulations around chemical constituents of these products, and marketing and age limits to prevent youth uptake of vaping. Abstract : Supplemental Digital Content is available in the text.